2022
DOI: 10.1248/bpbreports.5.3_59
|View full text |Cite
|
Sign up to set email alerts
|

Potential Ameliorative Effects of Kampo Medicines Ninjin’yoeito and Kamikihito on Frailty-Like Behavior in Naturally Aged C57BL/6J Mice

Abstract: Frailty is defined as an age-related decline in physiological reserve and increased vulnerability to stress. As frailty is a multifaceted condition, there is no effective pharmacotherapy for it yet. Ninjin'yoeito (NYT) and Kamikihito (KKT), traditional Japanese medicines (Kampo medicines), are promising in treating multifaceted conditions of frailty including fatigue and mental anxiety. However, their effects are still unclear. In this study, the effects of NYT and KKT on different types of frailty in naturall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Previous studies indicated that NYT exerted ghrelinneuropeptide Y (NPY) pathway-mediated appetiteenhancing effects [81][82][83] and increased blood albumin levels [84], thereby improving the nutritional state. Experiments using older mice and mouse aging models revealed that NYT inhibited muscle strength [85][86][87] and volume loss [85,88], and also prevented muscular telomere shortening [85]. Muscle protein synthesis was promoted and degradation was inhibited.…”
Section: Physical Frailtymentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies indicated that NYT exerted ghrelinneuropeptide Y (NPY) pathway-mediated appetiteenhancing effects [81][82][83] and increased blood albumin levels [84], thereby improving the nutritional state. Experiments using older mice and mouse aging models revealed that NYT inhibited muscle strength [85][86][87] and volume loss [85,88], and also prevented muscular telomere shortening [85]. Muscle protein synthesis was promoted and degradation was inhibited.…”
Section: Physical Frailtymentioning
confidence: 99%
“…Previous studies indicated that NYT ameliorated dementia or depression/anxiety [94][95][96] by increasing the levels of neurotrophic factors [94,97], attenuating the inhibition of neurogenesis [95,98], suppressing microglial overactivity [99], increasing cerebral blood flow [100], and enhancing cerebral glucose metabolism [92]. Furthermore, NYT improved diminished motivation [86,87,101,102] and suppressed the hypothalamic-pituitary-adrenal (HPA) axis by downregulating the sympathetic-adrenal-medullary (SAM) axis and GABA neurons to improve sociability [103].…”
Section: Psychological Frailtymentioning
confidence: 99%
See 1 more Smart Citation